Soluble CD146 in Heart Failure: Pathophysiological Role and Diagnostic Potential - Daniela Mocan; Radu Jipa; Daniel Alexandru Jipa; Radu Ioan Lala; Maria Puschita; Florin-Claudiu Rasinar; Diana-Federica Balta; Iulia-Silvia Groza; Amelia Uzum (Biomedicines)
Heart failure (HF) remains a major global health challenge, driven by multifactorial pathophysiological processes, such as systemic congestion, endothelial dysfunction, and inflammation. While natriuretic peptides are well-established biomarkers for diagnosing and monitoring HF, they do not fully capture the complexity of vascular involvement. CD146, also known as melanoma cell adhesion molecule (MCAM), is a transmembrane glycoprotein primarily expressed on endothelial cells and involved in cell adhesion, vascular permeability, and angiogenesis. Its soluble form (sCD146), released in response to multiple pathophysiological stimuli, including venous and arterial endothelial stretch, oxidative stress, and inflammatory cytokine activation, has emerged as a promising biomarker reflecting both hemodynamic congestion and systemic endothelial stress. This review synthesizes current knowledge on the structure, regulation, and release mechanisms of CD146 and explores its clinical utility in HF. Elevated sCD146 levels have been associated with echocardiographic and radiological indicators of congestion, as well as with adverse outcomes. While promising, its application is limited by variability, lack of standardization, and confounding elevations in non-cardiac conditions, including malignancy.